2021
DOI: 10.3390/plants10040804
|View full text |Cite
|
Sign up to set email alerts
|

Breeding of High Cooking and Eating Quality in Rice by Marker-Assisted Backcrossing (MABc) Using KASP Markers

Abstract: The primary goals of rice breeding programs are grain quality and yield potential improvement. With the high demand for rice varieties of premium cooking and eating quality, we developed low-amylose content breeding lines crossed with Samgwang and Milkyqueen through the marker-assisted backcross (MABc) breeding program. Trait markers of the SSIIIa gene referring to low-amylose content were identified through an SNP mapping activity, and the markers were applied to select favorable lines for a foreground select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 54 publications
0
18
0
1
Order By: Relevance
“…As reported by Moongngarm ( 2013 ), rice endosperm contains up to 70% of starch, which is not found in the cell wall itself. In other studies using a few samples, the starch content of rice milled grain was reported between 78.1 and 85.6% (Fujita et al, 2007 ) and 80 and 82% (Kim et al, 2021 ).…”
Section: Discussionmentioning
confidence: 87%
“…As reported by Moongngarm ( 2013 ), rice endosperm contains up to 70% of starch, which is not found in the cell wall itself. In other studies using a few samples, the starch content of rice milled grain was reported between 78.1 and 85.6% (Fujita et al, 2007 ) and 80 and 82% (Kim et al, 2021 ).…”
Section: Discussionmentioning
confidence: 87%
“…Simultaneously, the genetic basis of agronomic traits is also a scientific issue in determining crop promoting breeding programs (Pasam et al, 2012 ). In line with the two most commonly used methods in traits identification: (1) QTL mapping for crossed results (Skøt et al, 2005 ) and (2) association mapping between molecular markers and traits (Verdeprado et al, 2018 ), the breeding program is vital to identify the genes of interest for their efficient performance on agronomic traits (Kim M.-S. et al, 2021 ). A marker-assisted backcross selection employed by MABc was the most recent breeding method that not only potentially overcome conventional breeding limitations (Suh et al, 2013 ) but it can also speed up the genome recovery (99%) of recurrent-parent within three backcrosses (Miah et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…A marker-assisted backcross selection employed by MABc was the most recent breeding method that not only potentially overcome conventional breeding limitations (Suh et al, 2013 ) but it can also speed up the genome recovery (99%) of recurrent-parent within three backcrosses (Miah et al, 2015 ). A recent successful MABc program for ECQ rice was introduced through the functioning of SSIIIa gene responsible for low-AC, and the breeding program was mainly performed based on the identified fSNP (G/A) located on exon 3 of SSIIIa gene (Kim M.-S. et al, 2021 ). For the waxy gene, some functional alleles have long been measured for their performances in ECQ-related breeding development: G/T (at splice site of intron 1) introgression in Chinese male sterile hybrid rice (LTF-A and ZS-A) (Liu et al, 2006 ) and CT 17 transfer into II-32B lines for its low-AC (Jin et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result of their study indicated that the RPG was 80.11% for BC 1 F 1 , 95.30% for BC 2 F 1 and 95.9% for BC 2 F 2 [58]. Recently, Kim et al [59] applied KASP markers in foreground and background selection to select rice lines with a high cooking and eating quality in each backcross generation. The results indicated that KASP markers were efficient in identifying BC 1 F 1 and BC 2 F 1 plants with a high cooking and eating quality and in quickly recovering the RPG.…”
Section: Advantages Of Marker-assisted Gene Pyramiding/stacking 61 Speedy Recovery Of Recurrent Genome Parent (Rpg)mentioning
confidence: 99%